Difunctional Zn-SnS nanosheet as well as preparation method and application thereof

Through the photocatalytic-ion exchange technology of dual-function Zn-SnS nanosheets, the problem of difficulty in recovering Rh in the prior art is solved, and efficient and low-pollution Rh recycling is achieved, with good stability and recycling ability.

CN119793486AActive Publication Date: 2025-04-11EAST CHINA UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510286056.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-04-11
Estimated Expiration
2045-03-12

AI Technical Summary

Technical Problem

It is difficult for the prior art to effectively recover Rh from organic rhodium wastewater in the form of rhodium-organic ligand complexes, and the recycling method has problems such as serious volatility loss, serious pollution, complex operation, high operating costs and low recovery rates.

Method used

Dual-function Zn-SnS nanosheets are used to destroy the organic rhodium complex and degrade the organic ligands through photocatalytic technology, and at the same time, free Rh ions are recovered using ion exchange technology.

Benefits of technology

It has achieved efficient recycling of Rh from organic rhodium wastewater, with a recovery rate of more than 92%, reducing the harm to the environment, and the nanosheets have high stability and multiple recycling capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793486A_ABST
    Figure CN119793486A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photocatalysis-ion exchange, and particularly relates to a bifunctional Zn-SnS nanosheet and a preparation method and application thereof.The nanosheet is of a two-dimensional layered structure, and Zn < 2 + > is filled and distributed between layers of a two-dimensional [Sn3S7] n < 2 > n <-> framework; the preparation method comprises the following steps: carrying out ion exchange on a tin-containing layered metal sulfide and a zinc source, and then carrying out ultrasonic exfoliation in deionized water to obtain the nanosheet, the nanosheet is used as a photocatalysis-ion exchanger to break an organic rhodium complex, degrade an organic ligand and recover free rhodium. Compared with the prior art, the method solves the problem that in the prior art, Rh cannot be recycled from organic rhodium wastewater in a rhodium-organic ligand complex form through an ion exchange technology. According to the scheme, a photocatalysis technology and an ion exchange technology are combined, so that trace Rh is recycled from the organic rhodium wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalysis-ion exchange, and specifically relates to a dual-functional Zn-SnS nanosheet and a preparation method and application thereof. Background Art

[0002] Rhodium has stable resistance, good electrical and thermal conductivity, high catalytic activity, good acid and alkali corrosion resistance, and good high temperature oxidation resistance. Therefore, rhodium is widely used in high-tech, aerospace, military industry, petrochemical industry, fine chemicals, environmental protection and other fields, and plays an irreplaceable role. In particular, in chemical synthesis reactions, in homogeneous catalytic reactions, such as catalytic hydrogenation, carbonyl synthesis, hydroformylation and other chemical synthesis processes, rhodium homogeneous catalysts are required. With the continuous expansion of chemical synthesis capabilities, the amount of rhodium catalyst is also increasing; however, in the process of preparing organic rhodium homogeneous catalysts, a certain amount of organic rhodium wastewater will also be produced, and a large amount of organic rhodium wastewater will also be produced after the organic rhodium homogeneous catalyst fails.

[0003] The content of rhodium in the earth's crust is very low and the resources are very scarce. Therefore, it is necessary to recover rhodium from organic waste / wastewater to realize the resource utilization of rhodium. However, the raw materials, products and rhodium homogeneous catalysts used in the chemical catalytic process are all present in the same organic system. The rhodium-containing organic waste obtained after the reaction is of various types, the system is complex, the rhodium content in the wastewater is low, and the recovery is difficult. At present, the methods for recovering rhodium from waste organic catalysts include incineration, extraction, electrochemical method, membrane separation, biosorption, etc. However, these methods all have problems such as serious rhodium volatilization loss, serious pollution, complex operation, high operating cost, and low recovery rate to varying degrees. Therefore, it is a future development trend to develop a large-scale, industrialized process that is simple to operate, safe, has a high recovery rate, a wide range of adaptability, and is green and environmentally friendly, to achieve the recycling of rhodium, reduce environmental pollution, and improve the recovery rate of rhodium.

[0004] Ion exchange technology has been widely used in metal ion recovery. Experimental results show that [Me2NH2]2[Ga2Sb2S7]·H2O, [Et2NH2]2[Ga2Sb2S7]·H2O and [Me2NH2] 4 / 3 [Me3NH] 2 / 3Sn3S7·1.25H2O and other open framework sulfide complexes have high ion exchange capacity and excellent stability, such as: Efficient Removal and Recovery of Uranium by a Layered Organic–Inorganic Hybrid Thiostannate, J.Am. Chem. Soc. 2016, 138, 38, 12578–12585; A two-dimensionally microporous thiostannate with superior Cs + and Sr 2+ ion-exchange property, J. Mater. Chem.A, 2015, 3, 5665-5673; etc. Unfortunately, they cannot effectively recover Rh from organic rhodium wastewater in the form of rhodium-organic ligand complexes. Therefore, it is necessary to study a new, high-recovery, low-pollution rhodium recovery method. Summary of the invention

[0005] The purpose of the present invention is to provide a bifunctional Zn-SnS nanosheet and its preparation method and application in order to solve at least one of the above problems, so as to solve the problem that the prior art still cannot recover Rh from organic rhodium wastewater in the form of rhodium-organic ligand complexes by ion exchange technology. This solution combines photocatalytic technology with ion exchange technology to achieve the recovery of trace Rh from organic rhodium wastewater.

[0006] The purpose of the present invention is achieved through the following technical solutions: The first aspect of the present invention discloses a dual-functional Zn-SnS nanosheet, wherein the nanosheet is a two-dimensional layered structure, wherein Zn 2+ Filled and distributed in two dimensions [Sn3S7] n 2n- Between the layers of the skeleton.

[0007] Photocatalytic technology has attracted widespread attention due to its mild reaction conditions, simple operation, and direct use of sunlight. The Zn-SnS nanosheets have both ion exchange and photocatalytic functions. They can break the organic rhodium complex and degrade the organic ligand through the strong oxidizing property of the photocatalyst, providing the possibility for ion exchange recovery of Rh ions, and at the same time recovering free rhodium ions based on ion exchange.

[0008] Preferably, the nanosheet has a diameter of 1-10 μm and a thickness of 10-100 nm.

[0009] The second aspect of the present invention discloses a method for preparing the bifunctional Zn-SnS nanosheets as described above, wherein tin-containing layered metal sulfide is ion-exchanged with a zinc source, followed by ultrasonic exfoliation in deionized water to obtain the nanosheets.

[0010] Preferably, the tin-containing layered metal sulfide is FJSM-SnS; the zinc source is zinc sulfate and / or zinc chloride; and the dosage ratio of the tin-containing layered metal sulfide to the zinc source is 500 mg: 5-100 mmol / L.

[0011] Preferably, the FJSM-SnS is synthesized from tin chloride and elemental sulfur by a solvothermal method.

[0012] Preferably, the ion exchange is carried out in a chromatographic column, and the ion exchange time is 0.5 to 5 h.

[0013] Preferably, the ultrasonic power of the ultrasonic peeling is 50-500 W, and the ultrasonic time is 1-30 min.

[0014] The third aspect of the present invention discloses an application of the bifunctional Zn-SnS nanosheets as described above in the treatment of metal organic complex wastewater.

[0015] Preferably, in organic rhodium wastewater, the nanosheets act as a photocatalyst-ion exchanger to break the organic rhodium complex, degrade the organic ligand, and recover free rhodium.

[0016] Preferably, the complex breaking is carried out at a pH of 3 to 5.

[0017] Preferably, the nanosheets can also be regenerated and Rh ions recovered by reversible ion exchange, specifically: the used nanosheets (Rh ions stored between layers) are placed in a 1 mol / L ZnSO4 solution (pH adjusted to 2 with hydrochloric acid) for cleaning, so that the Rh ions stored between the nanosheet layers are exchanged with the Zn ions, thereby obtaining concentrated high-concentration rhodium and achieving the regeneration of the nanosheets at the same time.

[0018] The working principle of the present invention is: Through ion exchange, Zn 2+ In [Sn3S7] n 2n- The filling in the skeleton layer; and then through ultrasonic peeling, highly dispersed Zn-SnS nanosheets are obtained, so that the photocatalytic active sites and ion exchange sites are fully exposed, so that the Zn-SnS nanosheet photocatalyst-ion exchanger of this scheme has good catalytic performance and ion exchange performance.

[0019] The prepared two-dimensional Zn-SnS nanosheets can directly destroy complex organic rhodium molecules and obtain free Rh ions by photocatalytic degradation of organic ligands under visible light irradiation. At the same time, the obtained free Rh ions are continuously enriched and stored in [Sn3S7] through ion exchange. n 2n- The Rh ions are recovered in the framework. After the Rh ion storage is saturated, the Rh ions are recovered through reversible ion exchange, realizing the recovery of Rh resources and the recycling of catalysts.

[0020] Compared with the prior art, the present invention has the following beneficial effects: The invention prepares Zn-SnS nanosheet photocatalyst-ion exchanger by ion exchange and ultrasound. The raw materials are cheap and easily available, and the preparation method is simple and controllable. As a photocatalyst-ion exchanger for recovering rhodium from organic rhodium wastewater, it not only has high activity but also has good recycling stability.

[0021] Under visible light irradiation, the two-dimensional Zn-SnS nanosheets can recover more than 92% of Rh from the [(COD)RhCl]2 solution, and the removal rate of organic ligand COD can reach more than 86%. By effectively recovering trace amounts of Rh in organic rhodium wastewater, the harm to the environment is effectively reduced. In addition, in the cycle test, the two-dimensional Zn-SnS nanosheets also showed high stability, which provides the possibility for the efficient recovery of Rh in organic rhodium wastewater and the continuous removal of pollutants.

[0022] This scheme proposes a synergistic strategy of photocatalysis and ion exchange, which provides an effective way to recover Rh from organic rhodium wastewater. The two-dimensional Zn-SnS nanosheet photocatalyst-ion exchanger provided by the present invention can be recycled many times, and has low cost, simple process, and has large-scale application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a transmission electron microscope (TEM) image of the overall morphology of the Zn-SnS nanosheet photocatalyst-ion exchanger of Example 1; Figure 2 This is a transmission electron microscope energy spectrum scanning image of the Zn-SnS nanosheet photocatalyst-ion exchanger of Example 1; Figure 3 The activity test results of Zn-SnS nanosheet photocatalysis-ion exchanger for recovering Rh in [(COD)RhCl]2 solution, (a) is the concentration change of Rh ions, (b) is the concentration change of Zn ions; Figure 4 The concentration change of COD when Zn-SnS nanosheets photocatalyst-ion exchanger recovers Rh in [(COD)RhCl]2 solution; Figure 5The results of the cyclic test of Zn-SnS nanosheet photocatalysis-ion exchanger to recover Rh in [(COD)RhCl]2 solution, (a) is the recovery rate of Rh, and (b) is the removal rate of COD. DETAILED DESCRIPTION

[0024] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0025] The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product specifications. The reagents and raw materials used in the present invention are all commercially available.

[0026] This scheme proposes a method combining photocatalytic technology with ion exchange technology to recover trace Rh from organic rhodium wastewater.

[0027] A dual-functional Zn-SnS nanosheet, wherein the nanosheet is a two-dimensional layered structure, wherein Zn 2+ Filled and distributed in two dimensions [Sn3S7] n 2n- Between the layers of the skeleton. The diameter of the nanosheet is 1~10 μm and the thickness is 10~100 nm.

[0028] A method for preparing the bifunctional Zn-SnS nanosheets as described above comprises ion exchanging a tin-containing layered metal sulfide (FJSM-SnS) with a zinc source (ZnSO4 and / or ZnCl2, etc.), followed by ultrasonic exfoliation in deionized water to obtain the nanosheets.

[0029] in: Zinc source is 0.1~2 mol / L Zn 2+ The solution contains tin-containing layered metal sulfide and zinc source in a ratio of 500 mg:50 mL.

[0030] The tin-containing layered metal sulfide was synthesized by solvothermal method from SnCl4•5H2O and elemental S in the presence of dimethylamine: 0.502 g SnCl4•5H2O, 0.131 g elemental S, 3 mL dimethylamine (AR, 40 wt. % in H2O, Macklin) and 1 mL deionized water were fully mixed until uniform, and the resulting mixture was sealed in a 50 mL stainless steel reactor lined with polytetrafluoroethylene, transferred to an oven, heated at 180 °C for 3 days, and then cooled to room temperature to obtain yellow hexagonal crystals and fine yellow powder. The yellow crystals were washed with ethanol and dried to obtain the FJSM-SnS sample.

[0031] The ion exchange is carried out in the chromatographic column, and the ion exchange time is 0.5~5 h.

[0032] The ultrasonic power of ultrasonic peeling is 50~500 W, and the ultrasonic time is 1~30 min.

[0033] A bifunctional Zn-SnS nanosheet as described above is used as a photocatalyst-ion exchanger to photorecover rhodium from organic rhodium wastewater: during the reaction process, the pH of the reaction system is 3-5.

[0034] Example 1

[0035] 500 mg of FJSM-SnS crystals were filled in the chromatographic column, and 50 mL of 1.0 mol / L ZnSO4 solution was added for ion exchange for 2 hours. The obtained sample was then placed in 500 mL of deionized water and ultrasonically stripped at 100 W ultrasonic power for 5 min to obtain Zn-SnS nanosheet photocatalyst-ion exchanger, which was recorded as Zn-SnS-1.0-5 sample.

[0036] The product was tested as follows: Transmission electron microscopy (TEM) images such as Figure 1~2 As shown, the test instrument is FEI Talos 200s. Figure 1~2 It can be seen that the prepared Zn-SnS nanosheet photocatalyst-ion exchanger is a two-dimensional layered structure with a diameter of 1~10 μm. Figure 2 It can be found that Zn is uniformly dispersed on the photocatalyst-ion exchanger.

[0037] Example 2

[0038] The preparation method of Example 2 is the same as that of Example 1, with the only difference being that 500 mg of FJSM-SnS crystals are filled in a chromatographic column, 50 mL of 1.0 mol / L ZnCl2 solution is added for ion exchange, and then the obtained sample is placed in deionized water and ultrasonically stripped for 5 min to obtain a Zn-SnS nanosheet photocatalyst-ion exchanger.

[0039] Embodiment 3~embodiment 6 The preparation methods of Examples 3 to 6 are the same as those of Example 1, except that, unlike Example 1, the concentration of the ZnSO4 solution is 1.0 mol / L, the concentration of the ZnSO4 solution used in Example 3 is 0.1 mol / L, the concentration of the ZnSO4 solution used in Example 4 is 0.5 mol / L, the concentration of the ZnSO4 solution used in Example 5 is 1.5 mol / L, and the concentration of the ZnSO4 solution used in Example 6 is 2 mol / L.

[0040] Embodiment 7~embodiment 10 The preparation methods of Examples 7 to 10 are the same as those of Example 1, with the only difference being that, unlike Example 1, the ultrasonic stripping time is 5 min, the ultrasonic stripping time is 10 min in Example 7, 30 min in Example 8, 25 min in Example 9, and 1 min in Example 10.

[0041] Embodiment 11 to Embodiment 14 The preparation methods of Examples 11 to 14 are the same as those of Example 1, with the only difference being that, unlike Example 1, the ultrasonic stripping power is 100 W, the ultrasonic stripping power is 50 W in Example 11, the ultrasonic stripping power is 200 W in Example 12, the ultrasonic stripping power is 350 W in Example 13, and the ultrasonic stripping power is 500 W in Example 14.

[0042] Embodiment 15~embodiment 18 The preparation methods of Examples 15 to 18 are the same as those of Example 1, with the only difference being that, unlike Example 1, the ion exchange time is 2 h, the ion exchange time of Example 15 is 4 h, the ion exchange time of Example 16 is 5 h, the ion exchange time of Example 17 is 0.5 h, and the ion exchange time of Example 18 is 1.5 h.

[0043] Photocatalytic-ion exchanger activity test The recovery activity of the photocatalyst-ion exchanger for rhodium was measured by treating [(COD)RhCl]2 solution under a 300 W xenon lamp (λ>420 nm). 2 mg of the catalyst (the catalyst was the Zn-SnS nanosheet photocatalyst-ion exchanger prepared in Example 1) was added to a 100 mL reactor containing 100 mL [(COD)RhCl]2 solution (Rh content was 1 ppm, and the pH value was adjusted to 3 by 0.5 mol / L hydrochloric acid), and the temperature was controlled at 25 °C by condensing the circulating water, and stirred for a certain time (15 min) in the dark to reach adsorption equilibrium, and continued to stir and turn on the light for irradiation, and 5 mL of the mixed solution was taken out at different intervals (30 min, 60 min, 90 min, 120 min, 150 min), centrifuged, and the supernatant was obtained. After filtration, the concentrations of Rh and Zn were measured by ICP, and the COD concentration was measured by liquid chromatography, which was recorded as the visible light irradiation group.

[0044] The remaining steps remained unchanged, but the lights were not turned on during the whole process (equivalent to using only ion exchangers, which can only achieve the function of ion exchange). The concentration results of Rh and Zn obtained by testing were used to measure the COD concentration by liquid chromatography, which was recorded as the dark group.

[0045] Test results see Figure 3 and Figure 4 .

[0046] like Figure 3 As shown in the figure, in the experiment of recovering rhodium, the Zn-SnS nanosheet photocatalyst-ion exchanger demonstrated excellent rhodium recovery performance. After 150 minutes of visible light irradiation, the recovery rate of rhodium reached more than 92%. At the same time, the corresponding Zn ion dissolution was detected, proving the occurrence of the ion exchange process. The results of the dark group without light were significantly worse than those of the visible light group with light, indicating that the Zn-SnS nanosheets acted as both a photocatalyst (breaking the complex to obtain free rhodium ions) and an ion exchanger (ion exchange enrichment and recovery of free rhodium ions) in the process of recovering rhodium.

[0047] like Figure 4 As shown in the experiment of recovering rhodium, Zn-SnS nanosheet photocatalyst-ion exchanger also demonstrated efficient removal performance of organic ligand COD. After 150 minutes of visible light irradiation, the COD removal rate reached more than 86%.

[0048] Photocatalytic-ion exchanger cycle performance test The recovery activity of the photocatalyst-ion exchanger for rhodium was carried out by treating [(COD)RhCl]2 solution under a 300 W xenon lamp (λ>420 nm). 2 mg of the catalyst (the catalyst is the Zn-SnS nanosheet photocatalyst-ion exchanger prepared in Example 1) was added to a 100 mL reactor containing 100 mL [(COD)RhCl]2 solution (Rh content is 1 ppm, 0.5 mol / L hydrochloric acid adjusts its pH value to 3), and the temperature was controlled at 25 ° C by condensing the circulating water, and stirred for a certain time (15 min) in the dark to reach adsorption equilibrium, continued stirring and turned on the light for 150 min, and centrifuged. The obtained supernatant was filtered and the Rh concentration was measured by ICP, and the COD concentration was measured by liquid chromatography. The obtained precipitated sample was washed with 1 mol / L ZnSO4 solution (pH adjusted to 2 with hydrochloric acid) to regenerate the catalyst after ion exchange, centrifuged, and the above experiment was repeated after drying to determine the recycling performance of the catalyst.

[0049] Test results see Figure 5 .

[0050] like Figure 5 As shown, in the cycle experiment, the Zn-SnS nanosheet photocatalyst-ion exchanger exhibited excellent cycle stability, and the used Zn-SnS nanosheets could be regenerated and reused.

[0051] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A bifunctional Zn-SnS nanosheet, characterized in that: The nanosheet is a two-dimensional layered structure, wherein Zn 2+ Filled and distributed in two dimensions [Sn3S7] n 2n- Between the layers of the skeleton.

2. A bifunctional Zn-SnS nanosheet according to claim 1, characterized in that: The diameter of the nanosheet is 1-10 μm and the thickness is 10-100 nm.

3. A method for preparing the bifunctional Zn-SnS nanosheets according to claim 1 or 2, characterized in that: The tin-containing layered metal sulfide is ion-exchanged with a zinc source, and then ultrasonically exfoliated in deionized water to obtain the nanosheet.

4. The method for preparing a bifunctional Zn-SnS nanosheet according to claim 3, characterized in that: The tin-containing layered metal sulfide is FJSM-SnS; the zinc source is zinc sulfate and / or zinc chloride; the dosage ratio of the tin-containing layered metal sulfide to the zinc source is 500 mg: 5-100 mmol / L.

5. The method for preparing a bifunctional Zn-SnS nanosheet according to claim 4, characterized in that: The FJSM-SnS is synthesized from tin chloride and elemental sulfur through a solvent thermal method.

6. The method for preparing a bifunctional Zn-SnS nanosheet according to claim 3, characterized in that: The ion exchange is carried out in a chromatographic column, and the ion exchange time is 0.5 to 5 hours.

7. The method for preparing a bifunctional Zn-SnS nanosheet according to claim 3, characterized in that: The ultrasonic power of the ultrasonic peeling is 50-500 W, and the ultrasonic time is 1-30 min.

8. Use of the bifunctional Zn-SnS nanosheets as claimed in claim 1 or 2 in the treatment of metal organic complex wastewater.

9. The use according to claim 8, characterized in that: In organic rhodium wastewater, the nanosheets act as a photocatalyst-ion exchanger to break the organic rhodium complex, degrade the organic ligand, and recover free rhodium.

10. The use according to claim 9, characterized in that: The complex breaking is carried out at a pH of 3 to 5.

Citation Information

Patent Citations

  • Compound, preparation method and application thereof as ion exchange material

    CN104399538A

  • Novel antimony / bismuth-based transition metal layered chalcogenide material for harmful ion adsorption

    CN112536016A

  • Method for selectively recovering precious metal through photocatalysis of sulfur-containing compound organic salt solution

    CN117821760A